2009
DOI: 10.1016/j.jacc.2008.09.057
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Induced Post-Ischemic Left Ventricular Delayed Relaxation or Diastolic Stunning

Abstract: Detection of post-ischemic regional LV delayed relaxation or diastolic stunning after treadmill exercise using SI is a sensitive and reliable method for the detection of coronary artery disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(75 citation statements)
references
References 35 publications
1
73
0
1
Order By: Relevance
“…Delayed LV relaxation detected by radial strain from apical views (transverse strain) during the first third of diastole 5 and 10 minutes after exercise ("diastolic stunning") identified significant coronary stenosis with a sensitivity of 97% and specificity of 93%. 35 These encouraging data suggest that quantitative strain data are sensitive and provide incremental diagnostic information in DSE.…”
Section: Dobutamine Stress For Detection Of Coronary Artery Diseasementioning
confidence: 92%
“…Delayed LV relaxation detected by radial strain from apical views (transverse strain) during the first third of diastole 5 and 10 minutes after exercise ("diastolic stunning") identified significant coronary stenosis with a sensitivity of 97% and specificity of 93%. 35 These encouraging data suggest that quantitative strain data are sensitive and provide incremental diagnostic information in DSE.…”
Section: Dobutamine Stress For Detection Of Coronary Artery Diseasementioning
confidence: 92%
“…Recently, the strain imaging diastolic index (SI-DI) derived from transverse SI was demonstrated to be a sensitive marker to detect postischemic regional LV delayed relaxation or diastolic stunning, even after complete systolic functional recovery during stress echocardiography in CAD patients. 11) Furthermore, SI-DI was reported to be reduced even 24 hours after an ischemic event. 12) Similarly, using cardiac single-photon emission tomography with β-methyl-p-[…”
mentioning
confidence: 99%
“…For instance, tardokynesis has been completely characterized by strain in ischemic conditions [39]. In other studies from of our center [40,41] we have observed that torsion is diminished in patients with ischemia during exercise testing.…”
Section: Ischemia In Non-cadmentioning
confidence: 76%